ON JOHN RAWLS’ THEORY OF JUSTICE AND DAVID GAUTHIER’S MORALS BY AGREEMENT: A COMPARATIVE STUDY - Mohamed Taibi; Mohammed Adli (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
This paper explores and compares John Rawls’ Theory of Justice and David Gauthier’s Morals by Agreement to broaden the understanding of Justice. While acknowledging the elusive nature of a unified definition of Justice, this study explores historical justice ideologies, highlighting their complexities and limitations. It introduces the contrasting perspectives of Plato, Hobbes, Locke, and Rousseau, showcasing their impracticalities, moral biases, and narrow scopes in capturing societal fairness. Within this intricate web of divergent ideologies, Rawls’ emphasis on fairness and Gauthier’s advocacy for morality through rational agreements emerge as contemporary pillars in exploring Justice. The paper employs a structured comparative analysis methodology, drawing data from primary sources and enriching the understanding with secondary resources to conduct a meticulous exploration. The results shed light on Rawls’ focus on equal fundamental liberties and controlled inequalities as the foundation of Justice, juxtaposed against Gauthier’s concept of morality established through rational agreements and constrained maximization. Beyond highlighting differences, the study aims to reveal nuances, complexities, and potential convergences between these contemporary perspectives. By navigating historical justice theories and dissecting Rawls’ and Gauthier’s frameworks, this paper aspires to provide a comprehensive analysis, laying a robust foundation for comprehending the diverse landscapes of Justice in contemporary discourse.